MECHANISMS FOR INCREASING THE NOISE RESISTANCE OF ANALOG BLOCKS OF INFORMATION MEASURING SYSTEMS - Botirov Uchkun Vafokulovich (Galaxy International Interdisciplinary Research Journal, 2022)
Modern methods and means of data transmission are mainly aimed at transmitting large amounts of information at high speeds and relatively low noise and signal distortion in the communication line.